Micromineral Additives (Zinc, Selenium, Copper) and their Physiological Roles in Ruminant Nutrition: Article Review - Hassan , Shahla Fathola; Albayati, Husham jaafar musa (American Journal of Biology and Natural Sciences, 2025)
Indispensable to modern ruminant nutrition, microelement additives—the most important ones are zinc (Zn), selenium (Se), and copper (Cu)—serve the very need that requires them but remains a daily moving target. This review provides an integrative perspective on the current states of microelement physiology, deficiency and toxicity dynamics, and practical advice for supplementation. Good provision of Zn supports the integrity of the epidermis, immune responses, and the process of keratin formation; Cu drives both tissue respiration in mitochondria and the formation of connective tissues—as well as helping to make iron (Se) bioavailable. The Cu-Zn superoxide dismutase and Se glutathione peroxidase axis can operate by 30. Momentum is confirmed by field tests: through organic or hydroxy carriers, the bioavailability of these inorganic salts increased while the loss of Zn and Cu fecal reduced 15–25%. Though under heat stress, the additional antioxidant benefits from nano Se are now well attested. When blood or liver data are used in the management of production, adapted 'precision' feeding consistently emerges ahead of blanket supplementation by 0.05 kg energy corrected milk cow−1 day−1 to 0.09 kg energy corrected milk cow−1 day−1 and 40 g growth weight in lambs d−1. Environmental stewardship is still crucial: the retention rates of trace elements ingested are below 30%, and excess feeding leads to soil and water heavy metal problems. Future research needs are clear: these include models for breed-specific requirements, long-term nano mineral toxicokinetics, and how shifts in forage mineral density can be controlled through the effects of climate. What will the implementation of these new strategies mean to productivity or animal welfare? At first reading, one might think that these goals are incompatible. Only via integrated soil–plant–animal research programmes will it be possible to achieve equal consideration of both goals.